Desire for Visual Aesthetics (DVA) in the Store Environment: Concept and Measurement. (2nd January 2017) - Saran, Anshu; , Morris Kalliny; Minor, Michael
ABSTRACT: The article describes the development, purification, and validation of a reliable self-report scale designed to measure the Desire for Visual Aesthetics (DVA) in the store environment. There is limited literature on the subject and a measurement scale has eluded both academicians and practitioners that could help measure the need for aesthetics in the retailing environment and help marketers decide on the level and type of aesthetics for the different segments in the target market/s and also the different type of retail stores. We used 3 focus groups, 8 individual interviews, and 891 surveys to develop, purify, and validate the 9-item Likert type scale. We also provide evidence for dimensionality, reliability, and validity. The scale could be used by academicians and practitioners alike, and could replace single items to measure the concept.